2018
DOI: 10.1108/ils-03-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Library resources, student success and the distance-learning university

Abstract: PurposeResearch at the Open University Library Services in the United Kingdom has been investigating the relationship between access to online library resources and student success to help to understand whether there is a similar relationship at a distance-learning university to that found in other institutions. Design/methodologyThe study analysed online library resource data from access logs from the EZproxy and OpenAthens systems. A data set of 1.7 million online resource accesses was combined with student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Third, it is essential to monitor and evaluate the online learning process to find out the differences in students' participation and engagement (Nurse et al, 2018). Students with weak self-organization and self-regulation skills may need support and assistance from both teachers and parents.…”
Section: Resultsmentioning
confidence: 99%
“…Third, it is essential to monitor and evaluate the online learning process to find out the differences in students' participation and engagement (Nurse et al, 2018). Students with weak self-organization and self-regulation skills may need support and assistance from both teachers and parents.…”
Section: Resultsmentioning
confidence: 99%
“…It is more likely that the studies included in this meta-analysis have an effect, because studies that demonstrate impact are more likely to be published than those that do not (Borenstein et al 2009). Furthermore, in many of the studies reviewed, the introductions stated explicitly that the authors were seeking to confirm the same results as previous studies that ostensibly demonstrated that libraries have a positive impact on student outcomes (Chodock et al 2018;deJager et al 2018;Haddow & Joseph, 2010;Nurse et al 2018;Thorpe 2016). For this reason, meta-analyses in general are likely to overestimate the effect size compared to its theoretical true value.…”
Section: Meta-analysis Limitationsmentioning
confidence: 87%
“…5 In line with the wider organisational strategy, the library embarked upon research into library learning analytics in 2015, initially focussing on the relationship between library use and student performance or retention. 6 Following a platform provider change in 2017 to Adobe Connect, data on student attendance at online tutorials, and any subsequent views of sessions after the event, have been collected as part of the institutional learning analytics strategy. The availability of this data prompted the research team to investigate the relationship between attendance at the training sessions and student performance or retention.…”
Section: Learning Analytics At the Open Universitymentioning
confidence: 99%
“…Similar research was conducted at The Open University with comparable findings. 11 A few studies have been conducted replicating these methodologies with information literacy instruction attendance. At an individual student level, Wong and Cmor investigated the effect of library tuition on the student attainment score throughout the duration of their qualification.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation